Extending Microsoft Dynamics 365 for operations cookbook : extend the potential of your Dynamics 365 for operations implementation - Buxton, Simon (Packt Publishing, 2017)
Have the best tools at your fingertips to extend and maximize the efficiency of your business management About This Book Follow practical and easy-to-grasp examples, illustrations and coding to make the most out of Dynamics 365 for Operations in your business scenario Extend Dynamics 365 for Operations in a cost-effective manner by using tools you already have Solve common business problems with the valuable features of Dynamics 365 for Operations Who This Book Is For This book is for those who are getting to grips with Dynamics 365 for Operations developers or those migrating from C# development. The guide includes information essential for new and experienced Dynamics 365 for Operations developers. What You Will Learn Create enumerated and extended data types Understand the importance of using patterns and frameworks while creating a unique concept for your solution Service and deploy your code and packages to improve performance Write and perform unit tests to automate the testing process Design your security model and policies to provide code access privileges Construct the UI and business logic to add Power BI to dashboards In Detail Dynamics 365 for Operations is the ERP element of Microsoft's new Dynamics 365 Enterprise Edition. Operations delivers the infrastructure to allow businesses to achieve growth and make better decisions using scalable and contemporary ERP system tools. This book provides a collection of ?recipes? to instruct you on how to create - and extend - a real-world solution using Operations. All key aspects of the new release are covered, and insights into the development language, structure, and tools are discussed in detail. New concepts and patterns that are pivotal to elegant solution designs are introduced and explained, and readers will learn how to extend various aspects of the system to enhance both the usability and capabilities of Operations. Together, this gives the reader important context regarding the new concepts and the confidence to reuse in their own solution designs. This ?cookbook? provides the ingredients and methods needed to maximize the efficiency of your business management using the latest in ERP software - Dynamics 365 for Operations. Style and approach The book takes a practical recipe-based approach, focusing on real-world scenarios and giving you all the information you need to build a strong Dynamics 365 for Operations implementation.